From the Editors - Ilyas, Hamzah Puadi (Journal of ELT Research, 2017)
Welcome to the January 2017 issue of Journal of ELT Research. This issue, apart from celebrating New Year, is in coincidence with the happiness permeating across the University of Muhammadiyah Prof. DR. HAMKA’s (UHAMKA) campuses. The National Accreditation Board for Higher Education (BAN-PT) has officially announced that UHAMKA is accredited ‘A’ as an institution. This brings the consequence for the institution, and for us as an inseparable part of it, to keep progressing. As regards, we are determined to increase the quality and expand the coverage of this journal to reach wider readers. Our January 2017 issue touches several issues in ELT.